Analysis of MSME Loans on Economic Growth in Central Sulawesi in 2015-2022 - Elfine Louise Abu, Elfine Louise Abu; Yunus, Rita; Taqwa, Edhi; Sading, Yunus; Musdayati, M. (Golden Ratio of Data in Summary, 2024)
The role of small and medium enterprises in Central Sulawesi during 2015-2022 in creating added value continues to increase, thus MSMEs are considered to have a strategic role in helping reduce unemployment and poverty. The first role of MSMEs in the economy of Central Sulawesi is as a means of leveling the economic level of society, especially the lower middle class. The aim of th is research is to analyze the influence of MSME credit on economic growth in Central Sulawesi. This research uses a simple regression method. Based on research results, the increase in Gross Regional Domestic Product (GRDP) and economic growth in Central Sulawesi in 2015-2022 has a significant positive effect on the amount of MSME credit. According to statistical tests the amount of MSME credit contribute significantly by 0,000 or less than the 5% significance level. This shows that the distribution of MSME credit will help MSME players to develop their businesses, increase the number of workers, which will also increase output per business unit and per worker so that it will have an impact on economic growth.